The Fatimids and their successors in Yaman : the history of an Islamic community : Arabic edition and English summary of Idrīs ʻImād al-Dīn's ʻUyūn al-akhbār, vol. 7 /: the history of an Islamic community : Arabic edition and English summary of Idrīs ʻImād al-Dīn's ʻUyūn al-akhbār, vol. 7. al-subʻ 7 (2002) - Unknown
No abstract available